Mean platelet volume: A reliable marker of inflammation in recurrent apthous stomatitis and behçet disease? - Engin Senel; Bilal Acar; Emre Demir (Wolters Kluwer Medknow Publications, 2017)
Background: Mean platelet volume (MPV) is an indicator of platelet activation and aggregation. MPV has been found to be related with the inflammation of certain disorders in recent studies. Aims: We sought to investigate whether MPV could be an indicator of inflammation in patients with Behçet disease (BD) and recurrent apthous stomatitis (RAS). Materials and Methods: Our study was designed as a retrospective case-control study and data was retrieved from our institutional database. We randomly generated a total of three study groups from our clinical archive. All controls were sex and age-matched and randomly selected by computer. Eighty-five patients with BD, 82 patients with RAS, and 721 healthy controls were included for the study design. We compared mean MPV values in the patient groups and controls. Results: We found no difference in the mean MPV value between BD group and BD-control group. The mean MPV value was significantly higher in patients with RAS than that in the RAS-control group (9.11 ± 1.01 fL vs. 8.76 ± 1.15 fL, P = 0.045). There was no difference in mean MPV level between BD and RAS group. Conclusion: The association between MPV and inflammatory skin diseases such as BD and RAS should be investigated prospectively in case-control studies. Limitations: Retrospective study design.